2020
DOI: 10.1002/1878-0261.12670
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell‐based molecular subtypes and signature associated with clinical outcome in early‐stage lung adenocarcinoma

Abstract: Mast cells are a major component of the immune microenvironment in tumour tissues and modulate tumour progression by releasing pro-tumorigenic and antitumorigenic molecules. Regarding the impact of mast cells on the outcomes of patients with lung adenocarcinoma (LUAD) patient, several published studies have shown contradictory results. Here, we aimed at elucidating the role of mast cells in early-stage LUAD. We found that high mast cell abundance was correlated with prolonged survival in earlystage LUAD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 48 publications
(60 reference statements)
1
47
0
Order By: Relevance
“…Increasing evidence shows that the immune microenvironment is involved in the progression and malignancy of LUAD [16][17][18][19]. Immunotherapy serves as a promising therapeutic strategy for early-stage cancer patients with a low tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that the immune microenvironment is involved in the progression and malignancy of LUAD [16][17][18][19]. Immunotherapy serves as a promising therapeutic strategy for early-stage cancer patients with a low tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…85 Conversely, certain studies revealed that greater abundance of mast cells was related to better prognosis and prolonged survival in early-stage LUAD cases. 54,86 We also found relatively enhanced expression of CD4 and CD8A indicative of a strengthened immune response in the low-risk group. 7 Conversely, patients with high risk score had increased levels of immunosuppressive molecules (such as PD-L1, CTLA-4 and TIGIT).…”
Section: Discussionmentioning
confidence: 53%
“…A growing number of publications have demonstrated the complicated interaction between the immune microenvironment and the malignant transformation and development of LUAD. 54 TP53 mutant status is associated with the percentages of immune cell infiltration and the expression levels of immune checkpoints, which potentially serves as an indicator for evaluating the effectiveness of immunotherapy in LUAD. 55,56 Thus, reliable prognostic biomarkers associated with the tumor immune landscape and TP53 status potentially hold great promise for recognizing promising molecular targets and strengthening patient management in the era of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a recent publication [38] that the activation of natural killer cells promotes the efficacy of LUAD immunotherapy in mouse model by enhancing the adaptive immune responses. The abundance of mast cells was shown to be positively correlated with the survival of early-stage LUAD patients, and mast cells-related gene signatures can be used for predicting survival probabilities [39]. Moreover, it has been reported that the interaction between mast cells and natural killer cells is critical for anti-viral defense [40].…”
Section: Discussionmentioning
confidence: 99%